The Influence of Principal Leadership, Work Motivation, Work Discipline, and School Culture on Teacher Performance in MAS Ihya Ulumuddin, South Labuhanbatu - Jelita, Mei; Nasution, Novrihan Leily; Gulo, Nur'ainun (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
This research aims to determine the influence of school principal leadership, work motivation, work discipline, and school culture on teacher performance in Mas Ihya Ulumuddin. The total sample was 10 respondents. This research uses validity tests, reliability tests, classical assumption tests, multiple linear regression tests, t-tests, F tests, and coefficient of determination using SPSS 22. Based on the research results, it is known that the principal's leadership partially influences teacher performance, this can be seen from T calculated value > T table (4.309 > 2.228), work motivation influences teacher performance, this can be seen from the calculated T value > T table (4.979 > 2.228), work discipline influences teacher performance, this can be seen from the calculated T value > T table (4,601 > 2,228), school culture influences teacher performance, this can be seen from the calculated T value > T table (5,081 > 2,228). Simultaneously, the principal's leadership, work motivation, work discipline, and school culture influence teacher performance, this can be seen from the calculated F value > F table.